2014
DOI: 10.1016/j.jallcom.2014.05.181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of directional solidification rate on the microstructure and properties of deformation-processed Cu–7Cr–0.1Ag in situ composites

Abstract: Effect of directional solidification rate on the microstructure and properties Effect of directional solidification rate on the microstructure and properties of deformation-processed Cu-7Cr-0.1Ag in situ composites of deformation-processed Cu-7Cr-0.1Ag in situ composites Deping, "Effect of directional solidification rate on the microstructure and properties of deformation-processed Cu-7Cr-0.1Ag in situ composites" (2014). Faculty of Engineering and Information Sciences -Papers: Part A. 2966.Effect of direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The filament reinforcement phase was not yet completely formed at the beginning of the cold deformation, and the strength was mainly determined by the rule of mixtures. The strengthening was due to the work hardening of the Cu matrix [13,26,35]. For higher strains, the filament reinforcement phase was gradually formed, and the strength was primarily determined by the Hall-Petch relation [8,19,35].…”
Section: Cu-fe In-situ Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The filament reinforcement phase was not yet completely formed at the beginning of the cold deformation, and the strength was mainly determined by the rule of mixtures. The strengthening was due to the work hardening of the Cu matrix [13,26,35]. For higher strains, the filament reinforcement phase was gradually formed, and the strength was primarily determined by the Hall-Petch relation [8,19,35].…”
Section: Cu-fe In-situ Compositesmentioning
confidence: 99%
“…However, their strength and conductivity are decreased by the substantial solid solubility of Fe atoms in the Cu matrix at high temperatures, and the slow precipitation speed at low temperatures [7,8]. Their properties may be improved by multi-component alloying [8][9][10][11][12][13]. Wang et al [14], Song et al [15], and Xie et al [16] investigated the influence of Ag.…”
Section: Introductionmentioning
confidence: 99%
“…The directionally solidified alloy exhibited higher strength than the non-directionally solidified alloy under the same cooling rate 14,15 . Liu et al 16 reported that the tensile strength of the in situ composite from the directionally solidified alloy is significantly higher than that from the as-cast alloy.…”
Section: Introductionmentioning
confidence: 99%
“…[1, 27,32] The tensile strength and conductivity of the deformation-processed Cu-14Fe in situ composite with g = 7. …”
Section: Final Combination Of Strength and Conductivitymentioning
confidence: 99%